2014
DOI: 10.1097/aog.0000000000000372
|View full text |Cite
|
Sign up to set email alerts
|

Lymphedema After Surgery for Endometrial Cancer

Abstract: Objective To estimate lower-extremity lymphedema prevalence in patients surgically treated for endometrial cancer, identify predictors of lymphedema, and evaluate the effects of lymphedema on quality of life. Methods One thousand forty-eight consecutive patients who were operated on between 1999 and 2008 at Mayo Clinic were mailed a survey, which included our validated 13-item lymphedema screening questionnaire and two validated quality-of-life measures. Logistic regression models were fit to identify factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(92 citation statements)
references
References 31 publications
2
88
2
Order By: Relevance
“…Despite these findings, many agree that the identification of metastatic disease in the lymph nodes is critical in the diagnosis and treatment of women with endometrial cancer and lymph node metastases are an important prognostic factor in overall survival (4) (5). The use of sentinel lymph node (SLN) mapping plus ultra-staging could potentially maximize the identification of positive nodes, while minimizing the known risks of lymphadenectomy including longer surgical times, intraoperative injury, blood loss, and lymph edema (6, 7). …”
Section: Introductionmentioning
confidence: 99%
“…Despite these findings, many agree that the identification of metastatic disease in the lymph nodes is critical in the diagnosis and treatment of women with endometrial cancer and lymph node metastases are an important prognostic factor in overall survival (4) (5). The use of sentinel lymph node (SLN) mapping plus ultra-staging could potentially maximize the identification of positive nodes, while minimizing the known risks of lymphadenectomy including longer surgical times, intraoperative injury, blood loss, and lymph edema (6, 7). …”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive lymphadenectomy is associated with intraoperative complications, such as increased operating time, nerve and vessel injury, higher blood loss, and postoperative morbidity [8]. The rate of long-term lymphedema directly attributed to lymphadenectomy was recently reported to be 23% [9]. The morbidity associated with comprehensive lymphadenectomy is of particular concern in the low-risk population.…”
Section: Introductionmentioning
confidence: 99%
“…Two randomized trials found no difference in overall survival or progression free survival in patients who underwent surgical staging in clinically early stage EMCA with or without lymphadenectomy supporting the potential limitation of staging as a part of initial surgical management (34-36). Pelvic and para-aortic lymph node dissections can also lead to significant morbidity including lower extremity lymphedema, lymphocele formation, neurovascular damage, and increased risk of thrombotic events (37-41). …”
Section: Discussionmentioning
confidence: 99%
“…Despite studies validating the low-risk of nodal metastases in early stage EMCA patients using these different triage techniques and considering the potential added morbidity following pelvic and para-aortic lymph node dissection, there is not complete consensus within the Gynecologic Oncology community as to the best way to identify patients who need operative lymph node evaluation (18-24, 37-41). …”
Section: Discussionmentioning
confidence: 99%